The spoilers of Darfur: Sudan's protracted political crisis and the intensifying violence in Darfur are closely connected - Gerrit Kurtz (Stiftung Wissenschaft und Politik (SWP), 2022)
The Juba Peace Agreement of October 2020 has not pacified conflicts in Sudan, and has instead actually created new alliances between armed groups and security forces. After decades of marginalisation, conflict entrepreneurs from the periphery are now shaping Sudan's national politics and undermining the country's potential to return to democratic transition. Insecurity in Darfur could escalate and contribute to further destabilisation of the country. International donors should pressure these conflict entrepreneurs to relinquish power. They should also prudently promote projects to foster peace in Darfur at the same time.
urn:nbn:de:101:1-2022101012142035956637
Keywords: 320; Darfur; Sudan; Juba Peace Agreement (JBA); Sudanese Armed Forces (SAF); General Abdel Fattah al-Burhan; Rapid Support Forces (RSF); Lieutenant General Mohamed Hamdan Dagalo (Hemedti); UN-AU Mission in Darfur (UNAMID)